2006
DOI: 10.1210/en.2005-0880
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Spatiotemporal Expression of Prostaglandin F Synthase and Microsomal Prostaglandin E Synthase-1 in Porcine Endometrium

Abstract: Endometrial prostaglandins (PGs) and the PGE2/PGF2alpha ratio play an important role in regulating the estrous cycle and establishment of pregnancy. The enzymes downstream of cyclooxygenase-2 may determine the PGE2/PGF2alpha ratio in the porcine uterus. Thus, we have cloned porcine PGF synthase (PGFS) and microsomal PGE synthase-1 (mPGES-1) and characterized their expression in porcine endometrium during the estrous cycle and early pregnancy. PGFS and mPGES-1 amino acid sequences possessed a high degree (>67% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
79
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 72 publications
14
79
0
Order By: Relevance
“…However, another group reported that this difference in PGF 2a concentration in the ovarian-uterine vein is much less between cyclic and pregnant animals (Hunter & Poyser 1982). Our results indicate that the content of PGF synthase (PGFS) mRNA and/or protein in the conceptus and endometrium is decreased in the first day of maternal recognition of pregnancy, between days 10 and 13 compared with later stages of pregnancy (Waclawik et al 2006). However, after day 14 of pregnancy, content of PGFS mRNA and protein increases in both the endometrium and conceptus (Waclawik et al 2006, Waclawik & Ziecik 2007.…”
Section: Role Of Pgs During Pregnancy Establishmentmentioning
confidence: 54%
See 4 more Smart Citations
“…However, another group reported that this difference in PGF 2a concentration in the ovarian-uterine vein is much less between cyclic and pregnant animals (Hunter & Poyser 1982). Our results indicate that the content of PGF synthase (PGFS) mRNA and/or protein in the conceptus and endometrium is decreased in the first day of maternal recognition of pregnancy, between days 10 and 13 compared with later stages of pregnancy (Waclawik et al 2006). However, after day 14 of pregnancy, content of PGFS mRNA and protein increases in both the endometrium and conceptus (Waclawik et al 2006, Waclawik & Ziecik 2007.…”
Section: Role Of Pgs During Pregnancy Establishmentmentioning
confidence: 54%
“…Endometrial mPGES-1 expression exhibits a biphasic profile, corresponding with the profile of conceptus estrogen secretion (Waclawik et al 2006). Our recent results indicate that estrogen elevates PGE 2 synthesis and the PGE 2 :PGF 2a ratio by an increase of expression enzymes involved in PGE 2 synthesis (PTGS2 and mPGES-1) and a decrease in the content of enzymes involved in PGF 2a production (PGFS and CBR1) in the endometrium on days 11-12 after estrus (Waclawik et al 2009a).…”
Section: Role Of Pgs During Pregnancy Establishmentmentioning
confidence: 70%
See 3 more Smart Citations